Antecedents of maternal parenting stress: the role of attachment style, prenatal attachment, and dyadic adjustment in first-time mothers - Mazzeschi, Claudia; Pazzagli, Chiara; Radi, Giulia; Raspa, Veronica; Buratta, Livia (Frontiers in Psychology, 2015)
The transition to parenthood is widely considered a period of increased vulnerability often accompanied by stress. Abidin conceived parenting stress as referring to specific difficulties in adjusting to the parenting role. Most studies of psychological distress arising from the demands of parenting have investigated the impact of stress on the development of dysfunctional parent-child relationships and on adult and child psychopathology. Studies have largely focused on mothers’ postnatal experience; less attention has been devoted to maternal prenatal characteristics associated with the subsequent parental stress and studies of maternal prenatal predictors are few. Furthermore, no studies have examined that association exclusively with samples of first-time mothers. With an observational prospective study design with two time periods, the aim of this study was to investigate the role of mothers’ attachment style, maternal prenatal attachment to the fetus and dyadic adjustment during pregnancy (7th month of gestation) and their potential unique contribution to parenting stress three months after childbirth in a sample of nulliparous women. Results showed significant correlations between antenatal measures. Maternal attachment style (especially relationship anxiety) was negatively correlated with prenatal attachment and with dyadic adjustment; positive correlations resulted between prenatal attachment and dyadic adjustment. Each of the investigated variables was also good predictor of parenting stress three months after childbirth. Findings suggested how these dimensions could be considered as risk factors in the transition to motherhood and in the very beginning of the emergence of the caregiving system, especially with first-time mothers